Inovasi Produk Perbankan Syariah dalam Menjawab Kebutuhan Masyarakat Modern - Ihsan, Moh. (Program Studi Perbankan Syariah STAI Senori Tuban, 2024)
Rapid developments in the global economy have spurred Islamic banking to continuously innovate in providing products that are responsive to the needs of modern society. This article explores various product innovations in Islamic banking, including syndicated financing, trade finance, wealth management products, start-up financing, and business development. Syndicated financing emerges as an effective solution for large-scale projects requiring substantial funding, guided by principles of justice and sustainability. Meanwhile, trade finance offers financial instruments that facilitate international trade following Sharia principles. Wealth management products and start-up financing provide impetus for wealth management and initial funding for new businesses, based on principles of equity and shared risk. Moreover, innovative business development strategies expand the scope of Islamic banking services and strengthen its position in an increasingly competitive global market. The article also examines the positive impact of Islamic banking product innovations on financial inclusion and sustainable economic growth. By analyzing successes and challenges, this article provides deep insights into how innovations in Islamic banking products not only meet the demands of modern society but also reinforce the integrity and values underlying Sharia principles.